Anarchy - Peter, Arthur Louis (My University, 1896)
Introduction: The term anarchy is defined by many people, or classes of people, and in as many different ways. Take for instance the Anarchist himself, who says anarchy means personal liberty,” equal freedom, that is, every man is free to do that which he will, provided he does not infringes not the equal right or freedom of any other man. It means the reduction of the government to that stage where there is no law, or no power greater than his own. Anarchy means to him the carrying out of this plan and by any means possible. But again, what do the great comic writers and thinkers say is meant by anarchy? Probably it is best understood by Prof. Ely, who defines it as a social disease of a malignant type which tends and does to a certain extent break up society, tear down civilization, and reduces man to a barbarian and savage.
Citation: Peter, Arthur Louis. Anarchy. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Anarchy; Sociology; Political science; Theses; Manuscripts (documents)